1999
DOI: 10.1071/wr98074
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and population biology of long-nosed bandicoots (Perameles nasuta) at North Head, Sydney Harbour National Park

Abstract: The population biology, habitat utilisation and diet of a small, isolated population of long-nosed bandicoots (Perameles nasuta) was studied over a 22-month period at North Head in Sydney Harbour National Park, New South Wales. Reproductive output in this urban environment was high, with a mean litter size of 2.3 and production of up to four litters per year. The peak of reproductive activity was in late spring and early summer, with a cessation of breeding in late autumn or early winter. The main causes of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 0 publications
3
43
1
Order By: Relevance
“…The robustness of MCP estimates of home-range size are known to be limited and potentially biased (Börger et al 2006); however, the short period of attachment and consequent limited number of locations restricted more complex analysis such as kernel density estimates. Despite these limitations, our estimates of home-range size are broadly comparable with those recorded for bandicoots in the Peramelidae, where MCP home ranges of Perameles nasuta are reported as 1.8-2.0 ha (Scott et al 1999) and 4.0-4.2 ha (Hope 2012), and of Perameles gunni as 1.6 ha (Dufty 1994). Our estimates of short-term home range also appear plausible in comparison with results from spool-and-line tracking, where night-time ranges of five males ranged from 0.34 to 0.64 ha and males covered an average distance of 344 m (Anderson et al 1988).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The robustness of MCP estimates of home-range size are known to be limited and potentially biased (Börger et al 2006); however, the short period of attachment and consequent limited number of locations restricted more complex analysis such as kernel density estimates. Despite these limitations, our estimates of home-range size are broadly comparable with those recorded for bandicoots in the Peramelidae, where MCP home ranges of Perameles nasuta are reported as 1.8-2.0 ha (Scott et al 1999) and 4.0-4.2 ha (Hope 2012), and of Perameles gunni as 1.6 ha (Dufty 1994). Our estimates of short-term home range also appear plausible in comparison with results from spool-and-line tracking, where night-time ranges of five males ranged from 0.34 to 0.64 ha and males covered an average distance of 344 m (Anderson et al 1988).…”
Section: Discussionsupporting
confidence: 79%
“…In support of this, despite continued live trapping no further animals were captured within the ranges of animals tracked during our study. While this appears to be the case in our study, Anderson et al (1988) reported that ranges of male kalubu bandicoots overlapped and radio-tracking studies of the long-nosed bandicoot (Perameles nasuta) indicate that females had overlapping ranges throughout the year, whereas males displayed territorial behaviour to other males in non-breeding months but ranges overlapped during the breeding season (Scott et al 1999). Further studies at a range of sites and species, ideally utilising kernel density estimates of home range rather than MCP estimates, as the latter are often of limited utility in assessing temporal or spatial overlap between animals (Laver and Kelly 2008), will be necessary to determine whether intrasexual territoriality, as suggested by our study, is the norm for New Guinea's peroryctids.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Each species is preyed upon by both quolls and foxes (Alexander 1980;McKay 1994;Belcher 1995;Jones and Barmuta 1998), and all four species use scent-marking for intra-specific communication (Stoddart 1980;Gordon 1998;Scott et al 1999;Kerle 2001), indicating well developed olfactory abilities to support potential recognition of predators. We use the scat at trap technique used in many northern hemisphere studies to demonstrate odour avoidance by potential prey.…”
Section: Introductionmentioning
confidence: 99%